Sir Launfal: an echo to Breton Lays? - Fanny Moghaddassi (Etudes Epistémè)
Echoes are a distinguishing feature of Middle English Breton lays, which resound with many voices, and hinge around the problem of articulating repetition and variation. It is therefore appropriate that Sir Launfal, a late 14th century Breton lay by Thomas Chestre, should itself be fraught with echoes. The plotline actually insists on the crucial importance of speech, truth and lies in the fictional world. While the courtly world is consistently presented as a world of lies and gossip, Sir Launfal himself gradually emerges as a figure embodying truthfulness. The lay therefore pits distorted echoes, such as ring in both Arthur’s court, and the Mayor’s city, against faithful echoes, which characterise Launfal’s speeches. The hero’s misadventures at court fuel Chestre’s satiric representation of the courtly world, which he presents as a mere sham whereas he depicts Lady Tryamour as the epitome of truthfulness. In her, desire and fulfilment coincide, annihilating the painful gap between words and reality, desire and actual fact. She stands as Guenore’s symmetric opposite in the lay, and it is remarkable that her appearance at court marks the end of gossip, and re-establishes the truth. Nevertheless, Tryamour and Launfal’s departure at the end of the lay signals that truthfulness, ideal knighthood and courtesy do no longer exist in the human world. From this point of view, Sir Launfal departs from other Breton lays, displacing the knightly ideal from the courtly world into an inaccessible fairy land. Chestre’s poem is indeed but an echo to Breton lays.